INTERNALIZATION OF CORE VALUES OF STATE CIVIL APPARATUS (ASN) AS A STRENGTHENING OF ORGANIZATIONAL CULTURE AT THE DEPUTY FOR SUPERVISION AND CONTROL OF THE NATIONAL CIVIL SERVICE AGENCY (BKN) CENTRAL OFFICE - Josua Tarigan; Netty Laura S; Rutman L.Toruan (Universitas Kristen Indonesia, 2026)
The internalization of the fundamental values of the State Civil Apparatus (ASN) is an important aspect in strengthening organizational culture within the government environment. This study aims to analyze the process of internalizing the fundamental values of ASN implemented at the Deputy for Supervision and Control of the National Civil Service Agency (BKN) Central Office, as well as its impact on strengthening organizational culture. This research uses a qualitative approach with a descriptive qualitative method. Data were collected through in-depth interviews with ASN informants within the Deputy for Supervision and Control of BKN Central Office, direct observation of value internalization practices, and documentation studies of policies related to ASN ethics and work culture. Data analysis was conducted through data reduction, data presentation, and conclusion drawing to gain a deeper understanding of the value internalization process within the organization. The results show that the internalization of ASN fundamental values is carried out through various strategies such as value socialization, periodic training, and direct guidance from leadership. The main factors supporting this internalization process are strong leadership, clear policies, and active involvement of all ASN members. However, there are several challenges, such as resistance to change from certain individuals and weak mechanisms for continuous evaluation of the application of these values. The internalization of ASN fundamental values at the Deputy for Supervision and Control of BKN Central Office plays a significant role in shaping an organizational culture that is professional, accountable, and oriented toward public service. Therefore, it is necessary to enhance the implementation of more systematic and sustainable strategies to ensure the optimal internalization of these values.. Keywords: Internalization, Fundamental Values of ASN, Organizational Culture, BKN Central Office